Profil Leukosit dan Parasit Ikan Lele Mutiara (Clarias gariepinus) pada Media Kolam Beton, Kolam Terpal dan Ember - Naharuddin Sri; Alexander Simon Tanody; Yanse Yane Rumlaklak; I Gusti Komang Oka Wirawan; Sirajudin .; Kartono Gigih Nugroho; Muhammad Fajar Panuntun (JURNAL KAJIAN VETERINER, 2026)
This study aimed to evaluate the physiological responses and health status of pearl catfish (Clarias gariepinus) based on hematological parameters and parasite infestation under three culture systems: concrete pond (2×3×1 m, P1), tarpaulin pond (2 m diameter, P2), and 50 L bucket/budikdamber (P3), with rearing durations of 90, 70, and 80 days, respectively. Blood samples and swabs from gill mucus and intestinal fluid were collected 10 days before harvest to analyze differential leukocytes (monocytes, lymphocytes, heterophils) and identify parasites microscopically. Water quality measurements showed temperatures of 24–27°C, pH 7.0–7.1, and respiration ratios (R/CR) >1, indicating optimal environmental conditions. Lymphocyte percentages were highest in the concrete pond (67.67 ± 13.65%), followed by the tarpaulin pond (64.33 ± 19.76%) and bucket (59.00 ± 3.61%), but differences were not statistically significant (Kruskal–Wallis, p>0.05). Parasite identification revealed three species in the concrete pond (Trichodina sp., Gyrodactylus sp., Vorticella sp.), two species in the tarpaulin pond (Vorticella sp., Procamallanus sp.), and no parasites in the bucket. In conclusion, variations in culture systems influenced differential leukocyte profiles and parasite presence adaptively, without causing significant health disturbances. These findings provide a scientific basis for selecting culture systems that support immune health and welfare of pearl catfish.